Drama in prostor - Kralj, Lado (Primerjalna književnost, 1998)
Drama and space. - The paper advocates the thesis that every historical convention of stage space reflectively affects the dramatic writing. In other words: a dramatist usually writes under the strong influence of the general staging concept, as he sees it in the theatre of his days. Historically, the illusionist convention is predominant over the simultaneous, Elizabethan, abstract, play-within-a-play- and epis ones. The illusionist convention, which reached its peak at the end of the nineteenth century, is based on the contradictory belief that theatre needs to show the truth, and this can be achieved with the help of illusion, i.e. a deceiptive technique of showing merely imaginary characters, actions and places as though they were real. In this way, Aristotle's notion of probability was reinterpreted from causality into verism, and the reason for this process lies in the visual aspect of drama; Aristotle noticed the appealing offect of visuality, but he could not predict its later expansion. The simultaneous convention is an entirely different notion of space, typical of dramas written in the Middle Ages. It has no need of any illusion of reality, as its world is allegorical. A drama written for a simultaneous stage has the so-called implicit staging directions, which also occur in Elizabethan plays. They describe the scene by not being located in the secondary, but in the main text (dialogue) and therefore they anticipate the localisation of a fictitious space in the realm of the spectator's mind. One form of implicit stage direction is the so-called teichoscopia (a view from a wall) where a character looks outside the stage to a location which is not visible to the spectator, and describes the events taking place there. How much a dramatist was obliged to follow the stage convention of his days is also shown in the strict classicist rule of unity of place, which is mainly for one purpose: to protect the illusion of reality, since a change of place might actually destroy it.
Keywords: literarna teorija; literary theory; teorija drame; dramska zgradba; dramski prostor; teatrologija